Pengaruh Profitabilitas, Pengungkapan Tanggung Jawab Sosial Perusahaan dan Ukuran Perusahaan terhadap Nilai Perusahaan (Studi Kasus pada Perusahaan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Simbolon, Agustina Yohana; Sastrodiharjo, Istianingsih; Husadha, Cahyadi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This study aims to test the Influence of Profitability, Corporate Social Responsibility Disclosure, and Company Size on Company Value. The population in this study is all banking sector companies listed on the Indonesia Stock Exchange in 2019-2023. The variables used in this study are Company Value as a dependent variable; Profitability, Corporate Social Responsibility Disclosure, and Company Size as independent variables. The sampling technique used was the purposive sampling method and 140 data samples were obtained. The analysis methods used are Descriptive Statistical Analysis, Classical Assumption Test, Multiple Linear Regression Test and Hypothesis Test. The results of the study show that Profitability, Corporate Social Responsibility Disclosure, and Company Size have an effect on Company Value. The results of this literature review article are: 1) Profitability affects Company Value; 2) Corporate Social Responsibility Disclosure affects Company Value; and 3) Company Size affects Company Value.